Effect of treatment with humic acid (HA) on the growth of salt-stressed sweet basil plants (Journal of Hama University, 2025)
Research was carried out during the year 2024 in the village of Burj Al-Qasab - Latakia - Syria, by planting sweet basil seedlings in plastic bags that were distributed according to a randomized complete design (R.C.D) with three replicates. This research aimed to study the effect of spraying humic acid on the leaves of sweet basil plants at concentrations (1, 3 and 5 g/L) before irrigation with salt solutions prepared from sodium chloride (NaCl) at concentrations (6, 12 and 18) dS/m two weeks later. Measuring a set of morphological indicators (plant height (cm), number of branches (branch/plant), physiological indicators (total leaf surface area (cm2), photosynthesis rate (mg/cm2/day)), Biochemical indicators (chlorophyll content (µg/g fresh weight)) and proline content in leaves (µmol/g fresh weight). Treatment with salt stress led to negative effects that became more severe with increasing salinity concentration on all the morphological, physiological and biochemical characteristics studied, thus affecting the growth and development of the sweet basil plant.Treatment with humic acid, especially at two concentrations (1 and 3 g/l), led to an increase in plant height, number of branches, total leaf surface area, photosynthesis rate, and chlorophyll content in the leaves compared to the control and the other concentrations. It also led to an improvement in the proline content in the leaves compared to the control and treatments. Salinity and high concentration of humic acid, thus positively affecting the growth of the basil plant, and this applies to most of the criteria and characteristics studied. The initial treatment with humic acid, especially at a concentration of (1 g/l), improved the studied indicators under salinity conditions, especially at a low salinity concentration (6 dS/m) compared to the control and the rest of the treatments. Thus, increasing the tolerance of sweet basil plants to salt stress. Therefore, it can be suggested to use foliar spray treatments with humic acid at concentrations (1 and 3 g/l) for the purpose of improving the growth of the sweet basil plant and increasing its tolerance to salt stress.
Keywords: Tobacco seeds; Humic; salt stress